"All citizens of the world can save a life" — The World Restart a Heart (WRAH) initiative starts in 2018. (July 2018) - Böttiger, B.W.; Lockey, A.; Aickin, R.; Castren, M.; de Caen, A.; Escalante, R.; Kern, K.B.; Lim, S.H.; Nadkarni, V.; Neumar, R.W.; Nolan, J.P.; Stanton, D.; et al.
Abstract: "All citizens of the world can save a life". With these words, the International Liaison Committee on Resuscitation (ILCOR) is launching the first global initiative – World Restart a Heart (WRAH) – to increase public awareness and therefore the rates of bystander cardiopulmonary resuscitation (CPR) for victims of cardiac arrest. In most of the cases, it takes too long for the emergency services to arrive on scene after the victim's collapse. Thus, the most effective way to increase survival and favourable outcome in cardiac arrest by two- to fourfold is early CPR by lay bystanders and by "first responders". Lay bystander resuscitation rates, however, differ significantly across the world, ranging from 5 to 80%. If all countries could have high lay bystander resuscitation rates, this would help to save hundreds of thousands of lives every year. In order to achieve this goal, all seven ILCOR councils have agreed to participate in WRAH 2018. Besides schoolchildren education in CPR ("KIDS SAVE LIVES"), many other initiatives have already been developed in different parts of the world. ILCOR is keen for the WRAH initiative to be as inclusive as possible, and that it should happen every year on 16 October or as close to that day as possible. Besides recommending CPR training for children and adults, it is hoped that a unified global message will enable our policy makers to take action to address the inequalities in patient survival around the world.